Chronic Non-specific Low Back Pain and Motor Control During Gait - Koch, Cathrin; Hänsel, Frank (Frontiers in Psychology, 2018)
Background: Chronic non-specific low back pain (LBP) poses a major socioeconomic problem, although the mechanisms are not yet clear. Impaired motor control is one of the mechanisms being discussed. Objectives: The purpose of this review is to provide an overview of motor control parameter differences between individuals with and without non-specific LBP during gait. Methods: A literature search on Medline, SportDiscus, PsychInfo, PsychArticels, EMBASE and Scopus was performed. Twenty-nine articles comparing healthy adults and adults with chronic non-specific LBP in neuromuscular and/or biomechanical parameters during walking or running were examined. Data extraction and quality assessment were independently performed by two persons. Among others, we extracted population, conditions, outcome measures and results. Results: The results showed that persons with and without non-specific LBP differed in several parameters of motor control, which was indicated by a lower movement amplitude of the pelvis, more in-phase coordination, lower ground reaction forces, higher stride-to-stride variability and a higher activity in ES in the LBP group. Conclusion: Despite no strong evidence for any of the parameters, a combination of biomechanical and neuromuscular parameters provides a conclusive explanation. Impaired motor control during walking is reflected in higher activity of the erector spinae, which leads to a stiffened lumbar-pelvic region. Different acquisition and processing of data renders making comparisons difficult, whereby standards for future research are necessary.